Disease-Induced Mortality Outweighs Hunting in Causing Wild Boar Population Crash After African Swine Fever Outbreak - Morelle, Kevin; Bubnicki, Jakub; Churski, Marcin; Gryz, Jakub; Podgórski, Tomasz; Kuijper, Dries P. J. (Frontiers in Veterinary Science, 2020)
African swine fever (ASF) has been spreading in the Eurasian continent for more than 10 years now. Although the course of ASF in domestic pigs and its negative economic impact on the pork industry is well known, we still lack a quantitative assessment of the impact of ASF on wild boar (Sus scrofa) populations under natural conditions. Wild boar is not only a reservoir for ASF, it is also one of the key wildlife species affecting structure and functioning of ecosystems. Therefore, knowledge on how ASF affects wild boar populations is crucial to better predict ecosystem response and for the design of scientific-based wild boar management to control ASF. We used a long-term camera trap survey (2012-2017) from the Białowieża Primeval Forest (BPF, Poland), where an ASF outbreak occurred in 2015, to investigate the impact of the disease on wild boar population dynamics under two contrasting management regimes (hunted vs. non-hunted). Using random encounter model (REM), we showed that the density and abundance of wild boar dropped by 84 and 95% within one year following ASF outbreak in the unmanaged and managed area, respectively. In the managed area, we showed that 11-22% additional mortality could be attributed to hunting. Our study suggests ASF-induced mortality by far outweighs hunting-induced mortality in causing wild boar population decline and shows that intensified hunting in newly ASF-infected areas does not achieve much greater reduction of population size than what is already caused by ASF virus.